Potent and Selective Cytotoxic and Anti‐inflammatory Gold(III) Compounds Containing Cyclometalated Phosphine Sulfide Ligands. Issue 62 (30th September 2019) - Reddy, T. Srinivasa; Pooja, Deep; Privér, Steven H.; Luwor, Rodney B.; Mirzadeh, Nedaossadat; Ramesan, Shwathy; Ramakrishna, Sistla; Karri, Shailaja; Kuncha, Madhusudana; Bhargava, Suresh K.
Abstract: Four cycloaurated phosphine sulfide complexes, [Auκ 2 ‐2‐C6 H4 P(S)Ph2 2 ][AuX2 ] [X=Cl (2 ), Br (3 ), I (4 )] and [Auκ 2 ‐2‐C6 H4 P(S)Ph2 2 ]PF6 (5 ), have been prepared and thoroughly characterized. The compounds were found to be stable under physiological‐like conditions and showed excellent cytotoxicity against a broad range of cancer cell lines and remarkable cytotoxicity in 3D tumor spheroids. Mechanistic studies with cervical cancer (HeLa) cells indicated that the cytotoxic effects of the compounds involve the inhibition of thioredoxin reductase and induction of apoptosis through mitochondrial disruption. In vivo experiments in nude mice bearing HeLa xenografts showed that treatment with compounds 4 and 5 resulted in significant inhibition of tumor growth (35.8 and 46.9 %, respectively), better than that of cisplatin (29 %). The newly synthesized gold complexes were also evaluated for their in vitro and in vivo anti‐inflammatory activity through the study of lipopolysaccharide (LPS)‐activated macrophages and carrageenan‐induced hind paw edema in rats, respectively. Abstract : Dual benefits ! Four new cycloaurated complexes, [Auκ 2 ‐2‐C6 H4 P(S)Ph2 2 ]X [X=AuCl2, AuBr2, AuI2, PF6 ], show excellent cytotoxicity against a broad range of cancer cell lines as well as anti‐inflammatory activity in both in vitro and in vivo studies (see figure). Mechanistic studies indicated that the cytotoxic effects of the compounds involve the inhibition of thioredoxin reductase and induction of apoptosis through mitochondrial disruption.